Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 747 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Euphorbia corollata L.", "Geometry POLYGON((-109.20 22.72,-109.20 50.32,-54.10 50.32,-54.10 22.72,-109.20 22.72))", "HasGeospatialIssue is false" ] } The dataset includes 747 records from 30 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000782-160526112335914/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences